Pengaruh Suhu Lingkungan di Kota Solok terhadap Suhu Rektal, Konsumsi Pakan dan Konsumsi Air Minum Burung Puyuh (Coturnix coturnix japonica) - Alfian Asri; Harissatria (Program Studi Peternakan, 2021)
This study aims to find out the effect of ambient temperature in the city of Solok on rectal temperature, feed consumption, and drinking water consumption of quails. The quail in this study aged 5 weeks old. They were obtained from a quail breeding in Nagari Cupak, Solok. The applied design was a completely randomized design (CRD) in which average ambient temperatures for each treatment were 22.63 ± 1.04°C in the morning, 32.14 ± 1.37°C in the midday,31.02 ± 1.28°C in the afternoon, and 25.46 ± 0.66°C in the evening. Each treatment was repeated 4 times. The variables measured were rectal temperature, feed consumption, and drinking water consumption. The results indicated that the ambient temperature in the midday and afternoon significantly increased rectal temperature and drinking water consumption compared to those in the morning and evening. However, the ambient temperature in the midday andafternoon significantly decreased feed consumption compared to that in the morning and evening. It can be concluded that the ambient temperature in the city of Solok affects rectal temperature, feed consumption, and drinking water consumption of quails.